Comparison between Capsule Endoscopy and Magnetic Resonance Enterography for the Detection of Polyps of the Small Intestine in Patients with Familial Adenomatous Polyposis - E. Akin; A. Demirezer Bolat; S. Buyukasik; O. Algin; E. Selvi; O. Ersoy (Gastroenterology Research and Practice)
Objective. The objective of this study was to assess the utility of magnetic resonance enterography (MRE) compared with capsule endoscopy (CE) for the detection of small-bowel polyps in patients with familial adenomatous polyposis (FAP). Methods. Patients underwent MRE and CE. The polyps were classified according to size of polyp: <5 mm (small size), 5–10 mm (medium size), or >10 mm (large size). The location (jejunum or ileum) and the number of polyps (1–5, 6–20, >20) detected by CE were also assessed. MRE findings were compared with the results of CE. Results. Small-bowel polyps, were detected by CE in 4 of the 6 (66%) patients. Three patients had small-sized polyps and one patient had medium-sized polyps. CE detected polyps in four patients that, were not shown on MRE. Desmoid tumors were detected on anterior abdominal wall by MRE. Conclusion. In patients with FAP, CE can detect small-sized polyps in the small intestine not seen with MRE whereas MRE yields additional extraintestinal information.